Reduction in the number of lut elements for control units with code sharing - Barkalov, Alexander; Titarenko, Larysa; Bieganowski, Jacek (Zielona Góra: Uniwersytet Zielonogórski)
Two methods are proposed targeted at reduction in the number of look-up table elements in logic circuits of compositional microprogram control units (CMCUs) with code sharing. The methods assume the application of field-programmable gate arrays for the implementation of the combinational part of the CMCU, whereas embedded-memory blocks are used for implementation of its control memory. Both methods are based on the existence of classes of pseudoequivalent operational linear chains in a microprogram to be implemented. Conditions for the application of the proposed methods and examples of design are shown. Results of conducted experiments are given.
Keywords: compositional microprogram control unit; code sharing; operational linear chain; field-programmable gate arrays; look-up table; design; embedded-memory block